Study of blood lead and semen lead concentration in male infertility (Pulse, 2011)
Objective: To evaluate the association of blood and semen lead with male  infertility. Design: It was a case control study carried out in the department of Biochemistry, BSMMU, from January, 2004 to December, 2004.Subjects: Of 52 male subjects, 26 were infertile with oligospermia and / or asthenospermia. Age matched 26 normospermic subjects with normal standard semen parameters (volume, count, motility and morphology) were selected as controls. None had the history of occupational exposure to lead.Results: Median values of blood lead were 19.96 µg/dl and 17.68 µg/dl (normal